2022
DOI: 10.3390/healthcare10050874
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Statewide Mandatory Medicaid Managed Care (SMMC) Programs on Hospital Obstetric Outcomes

Abstract: The state of Florida implemented mandatory managed care for Medicaid enrollees via the Statewide Medicaid Managed Care (SMMC) program in April of 2014. The objective of this study was to examine the impact of the implementation of the SMMC program on the access to care and quality of maternal care for Medicaid enrollees, as measured by several hospital obstetric outcomes. The primary data source for this retrospective observational study was the Hospital Cost and Utilization Project (HCUP) all-payer State ED (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…For the full report, our electronic searches yielded 25 973 citations (Figure). We screened 589 full-text articles, of which 28 studies, reported in 29 articles, were eligible for the current systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For the full report, our electronic searches yielded 25 973 citations (Figure). We screened 589 full-text articles, of which 28 studies, reported in 29 articles, were eligible for the current systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…One study (Symum et al) reported on unplanned health care utilization (eAppendix 7 in Supplement 1). Florida’s Mandatory Medicaid Managed Care policy was associated with a lower rate of preventable readmissions (incidence rate ratio [IRR], 0.86; 95% CI, 0.80 to 0.93) and emergency department visits (IRR, 0.87; 95% CI, 0.82 to 0.93) by 1.5 months post partum …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations